Teeth complexity, hypsodonty and body mass in Santacrucian (Early Miocene) notoungulates (Mammalia) - Cassini, Guillermo H. (2017)
Fil: Cassini, Guillermo H.. División Mastozoología. Museo Argentino de Ciencias Naturales Bernardino Rivadavia. CABA, Argentina